Factors affecting employees’ engagement : a study on Bank Islam Malaysia Berhad (BIMB) Terengganu employees' / Nuri Azaliah Mohd Maidin & Hayatul Akmal Mohamed - Mohd Maidin, Nuri Azaliah; Mohamed, Hayatul Akmal (2017)
Employees’ engagement is an imperative method in any organization that seeks competent human resources. The issue, in recent years however, has developed to be one of the most sensitive issued in services industry. Moreover this research opted for solutions, as to what are the main factors affecting employees' engagement, in particular, the banking sector. Objective of this research were grounded on finding the relevant factors affecting employees' engagement. Four factors were established as benchmarks for the research purpose, namely financial reward, team climate, participation in decision making and career advancement. We have adopted Parasuramanet.al. (1998) as our research frameworks. The focus of this research is on Bank Islam Malaysia Berhad's (BIMB) employees in Terengganu, and the sample size were taken from the population of white collar worker in BIMB Terengganu. A total of 118 questionnaires were disseminated to each branch in Terengganu. Including Kemaman Branch. Dungun Branch, Jalan Sultan Ismail Branch, Padang Hiliran Branch. Kuala Nerus Branch. Regional Office and Jerteh Branch. The finding of this research show team climate and participation in decision making effectively determines employees' engagement, while financial reward and career advancement pose no significance to such engagement.